Law of Protection of Children under Various Religions - Fraz Ashraf Khan; Arslan Raza (Journal of Religion and Society, 2025)
The protection of children is a universal concern, deeply embedded in the doctrines and practices of major world religions. This paper explores the safeguarding of children during times of conflict and post-war recovery across Islam, Christianity, Hinduism, Judaism, Sikhism, and Buddhism. By analyzing scriptural mandates, historical precedents, and contemporary organizational efforts, this study highlights the ethical imperatives and practical interventions inspired by religious teachings. Through qualitative content analysis, the research demonstrates that faith-based doctrines not only advocate for the protection and nurturing of children but also guide the humanitarian responses and rehabilitation programs that support child welfare in crisis. Ultimately, the paper shows that religious frameworks provide both immediate relief and long-term strategies for the welfare, healing, and empowerment of children affected by conflict. Keywords: Protection, Children, War/Armed Conflict, Islam, Islam, Christianity, Hinduism, Judaism, Sikhism, and Buddhism.